The Effect of Geometrical Shape of Surface Texture on the Rheology and Tribology of Confined Lubricants - Fankai Peng; Ahmad Jabbarzadeh (Lubricants)
Understanding lubrication at the nanoscale is essential for reducing friction. While alkanes, the primary component in most lubricants, have been studied for their molecular structure’s impact on rheology and behavior when confined by solid surfaces, the influence of confining surface texture remains underexplored. This research uses molecular dynamics simulations to investigate the rheological behavior of thin film lubrication between various patterned rough surfaces. The study focuses on sinusoidal, sawtooth, and squaretooth wave-patterned surfaces, using hexadecane as the lubricant. The simulations examine the effects under different normal loads and shear rates. Surface patterns significantly influence the formation and structure of crystalline bridges, depending on shear rates and normal loads. The sawtooth wave-patterned surface exhibits the highest viscosity under low normal load and shear rate conditions, forming crystalline bridges with a molecular orientation perpendicular to the shear direction. The squaretooth patterns exhibit the lowest viscosities due to the nematic order in crystalline bridges with molecules aligned in the shearing direction. The sinusoidal wave-patterned surface shows intermediary viscosity with disordered crystalline bridge groups formed with random molecular orientation. The lowest viscosity provided by the squaretooth pattern surface persists across various conditions, including both transitory and steady states, under high and low loads, and over a wide range of shear rates. However, the difference in shear viscosity is reduced at higher normal loads. This research provides valuable insights for designing nanoelectromechanical systems (NEMS) and other applications where boundary conditions are critical to lubrication.